Proposed Business Strategy of Bank XYZ In Retaining Non Captive Loyal Customer Through Customer Satisfaction - Setiawan, Aef; Toha, Moh (The Indonesian Journal of Business Administration, 2015)
Abstract. In order to compete successfully in today’s dynamic business environment, many  top performing banks always look into the needs and demands of their customers. This is the reason why many researchers have continuously emphasized on the importance of customer satisfaction and loyalty. Quality Services has become customer satisfaction aspect and proven by some researchers. Others used the dimensions  to evaluate customer satisfaction. This research attempts to find the correlation of customer satisfaction on customer loyalty then proposed business strategy of Bank XYZ in retaining loyal customer through service and product customer satisfaction. The data were collected from 130 customers of bank XYZ who visiting the banks counters. The collected data then analyzed using Statistical analysis. The business strategy is proposed using diamond strategy that consist of arena, differentiator, vehicle, staging and economic logic. The results of the study showed that customer satisfaction was positively impacted to customer loyalty. Thus the service dimensions that can differentiate are Tangible, Empathy and Product itself. Key Words: Customer Satisfaction, Customer Loyalty, Banking, Service Quality, Service Quality Dimension, Diamond Strategy, Business Model.